Development of Lipid Nanoparticles for Delivery of siRNA as Gene Therapy for Lung Cancer - Miksusanti Miksusanti; Rafiullah Amin; Amir Raza (Journal of Biomedical and Techno Nanomaterials, 2024)
Lung cancer remains a significant health challenge with high mortality rates, necessitating innovative treatment approaches. Lipid nanoparticles (LNP) offer a promising platform for the delivery of small interfering RNA (siRNA) as gene therapy to target specific oncogenes in lung cancer cells. To develop and optimize LNPs for efficient siRNA delivery, improving gene silencing efficiency and therapeutic outcomes in lung cancer treatment. The study involved in vitro and in vivo experiments to characterize the LNPs, evaluate gene silencing efficiency, and assess therapeutic efficacy. LNPs were formulated with specific lipid compositions and tested on lung cancer cell lines and murine models. Optimized LNP formulations demonstrated high siRNA encapsulation efficiency (>85%), stable particle size (80-120 nm), and suitable zeta potential (-30 to -50 mV). In vitro studies showed over 70% gene silencing efficiency, while in vivo experiments indicated significant tumor growth inhibition and improved survival rates in murine models. Biodistribution studies confirmed targeted delivery to lung and tumor tissues with minimal off-target effects. The study highlights the potential of LNP-siRNA therapy as an effective and specific treatment for lung cancer. Further research and clinical trials are needed to validate these findings and optimize the delivery system for clinical use.